Promoting carbon neutrality in China: do financial development, foreign direct investment, and industrialization play a material role? - Yan, Jun; Li, Kaodui; Musah, Mohammed; Zhang, Lijuan; Zhou, Yutong; Gao, Dan; Akwasi Nkyi, Joseph; Gyimah Sackey, Frank; Attah Kumah, Emmanuel; Cao, Siqi; Yao, Linnan (Frontiers in Environmental Science, 2024)
One of the crucial issues confronting China is high carbon dioxide (CO2) emissions. As a result, the nation has outlined various measures to help curb the increasing rate of pollutant emissions. This study seeks to examine the linkage between foreign direct investment, industrialization, financial development, and environmental sustainability in China, to offer policy options to help drive the carbon neutrality agenda of the nation. In attaining this goal, a time series data over the period 1990 to 2018 is employed. From the results, the investigated variables have an I(1) integration order and possess a long-term cointegration association. The fully modified ordinary least squares (FMOLS) technique is employed to examine the parameters of the determinants and from the results, foreign direct investment deteriorates ecological sustainability via more CO2 emissions. This finding validates the pollution haven hypothesis. Also, industrialization and financial development are not friendly to the nation's environmental quality. Furthermore, economic growth and urbanization promote pollution in the nation. Besides, the interaction between financial development and foreign direct investment, and between financial development and industrialization promote pollution in the country. Moreover, foreign direct investment and financial development have an inverted Ushaped association with environmental degradation, but industrialization is not nonlinearly associated with pollutant emissions. Sensitivity analysis via the dynamic ordinary least squares (DOLS) and canonical cointegration regression (CCR) uphold the above discoveries. Based on the findings, policy recommendations to help the country attain its carbon-neutrality targets are proposed.